Comparative analysis of soil and water dynamics in conventional and sod-based crop rotation in Florida - Acharya, Bibek; Sharma, Vivek (Frontiers in Agronomy, 2025)
Analyzing soil water dynamics is crucial for the advancement of sustainable agriculture, encompassing crop growth management, soil health preservation, and the strategic use of resources. This study assessed the impact of conventional and sod-based crop rotations on water dynamics within the Suwannee River Basin’s unique karst and sandy soil environment from 2019-2022. The study was conducted on a 16-hectare center pivot irrigated field, featuring two conventional crop rotations: one comprising maize (Zea mays) and peanut (Arachis hypogaea), and another including maize, carrot (Daucus carota), and peanut. In addition, two sod-based rotations were evaluated: one involving two years of bahiagrass (Paspalum notatum) followed by maize and peanut, and another comprising two years of bahiagrass succeeded by maize, carrot, and peanut. The results indicated that maize maintained consistent crop water productivity (WPC-ETc) at 2.6 kg m-3 across rotations, while WPC-ETc for peanuts ranged from 1.5 kg m-3 for conventional rotation and 1.1 kg m-3 for sod-based. The cumulative crop evapotranspiration (ETc) for maize throughout the years was on an average 477 mm (Standard Deviation (SD) = 44 mm), while peanuts showed an average cumulative ETc of 354 mm (SD = 39 mm). Carrots and bahiagrass recorded cumulative ETc values in the range of 225-259 mm and 1611 mm (over two years), respectively. Deep percolation accounted for 31% of total water input, which emphasizes the need for strategic water management in porous soils. Additionally, sod-based rotations increased field capacity by 32%, soil organic carbon (SOC) by 31% in the top 15 cm, and soil aggregate stability by 101%, enhancing soil structure and moisture conservation. This study highlights sod-based rotations as effective for soil and water conservation, offering practical strategies for water-efficient agriculture in similar ecosystems.